Islamic Social Responsibility and Islamic Corporate Governance in Influence Financial Performance Using Sharia Conformity and Profitability - Vilantika, Elok; Handayani, Anita (LAA MAISYIR: Jurnal Ekonomi Islam, 2023)
This study aims to examine and analyze the relationship between Islamic Social Responsibility (ISR) and Islamic Corporate Governance (ICG) on financial performance using Sharia Conformity and Profitability (SCnP). The research population is Sharia Commercial Banks registered with the Financial Services Authority in 2017-2022, totaling 13 Sharia Commercial Banks selected using a purposive sampling method with certain criteria. Regression factor analysis, a hybrid of factor analysis and multiple linear regression, is the data analysis technique used in this study. The results of factor analysis show that each variable's indicator is responsive to the general trend and prepared for additional study. It is possible to conclude that ISR and ICG positively affect the financial labor performance that SCnP has calculated based on the regression analysis of many lines. Sharia banking with strong ISR and ICG reporting will also have strong financial results.